Impact of the Solar System's passage through dark molecular clouds: a case of local habitability - Leão, Jurandi; Bentes, Thays; Vilas-Boas, Jose Williams; Wuensche, Carlos Alexandre (Cadernos de Astronomia, 2023)
Molecular clouds (MC) are non-homogeneous, neutral regions, with volumetric densities ranging from 102 cm-3 to 108 cm-3, visible extinctions up to 30 mag, and temperatures ranging from 10 to 100 K. The Solar System lies in a low-density plasma bubble, surrounded by dark MC distributed in a radius of ~ 100 pc. In its motion in the Galactic plane, the Solar System must traverse one or more of these regions at each orbit around the galactic center. This paper discusses the impact of the Sun being immersed in an MC and analyzes the effects of solar radiation that hits the Earth as a function of the density of the region traversed. For MC volumetric densities in the order of 104 cm-3, the ionization front reaches a region of 1 astronomical unit (UA) in about 2 days. If the density is greater than 106 cm-3, all ionizing UV photons are consumed in a spherical volume with radius less than 1 UA, significantly cooling the Earth in its trajectory around the Sun. If the SS enters an interstellar cloud with a density greater than or equal to 107 cm-3, the UV radiation (that reaches Earth in approximately 300 days will be blocked) or it may remain in this state indefinitely if the cloud density is higher. Under these conditions, the Earth would come into existence in an environment with characteristics of the Interstellar Environment, which would have catastrophic consequences for the planet's climate.
Keywords: Habitability; molecular clouds; astrobiology